2018
DOI: 10.1002/casp.2357
|View full text |Cite
|
Sign up to set email alerts
|

The buffering role of in‐group identification and intergroup contact on the association between perceived discrimination and mental health

Abstract: Previous research has shown that disadvantaged group members cope with the negative effects of perceived discrimination (PD) on mental health using various mechanisms. We examined the potential protective role of two processes—in‐group identification and intergroup contact—on the association between PD and mental health (anxiety and depression) among physically disabled adults (N = 269, Mage = 39.13, SD = 13.80). Intergroup contact, but not in‐group identification, had a buffering role on the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
(76 reference statements)
1
6
0
Order By: Relevance
“…Begeny and Huo (2017) found that minority-group members with greater group identity centrality tended to perceive more discrimination and social threats, which negatively affected their psychological health (see also Rubin & Stuart, 2018; Sellers & Shelton, 2003). These findings are in line with those showing that minority-group members highly identified with their ingroup were more vulnerable to the effect of perceived discrimination or other social threats (Bagci et al, 2018b; Eccleston & Major, 2006; Major, Quinton, & Schmader, 2003; McCoy & Major, 2003; Noh, Beiser, Kaspar, Hou, & Rummens, 1999; Yoo & Lee, 2008). Social exclusion would thus greatly affect the psychological condition of those immigrants who are mostly connected and in turn identified with other immigrants.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Begeny and Huo (2017) found that minority-group members with greater group identity centrality tended to perceive more discrimination and social threats, which negatively affected their psychological health (see also Rubin & Stuart, 2018; Sellers & Shelton, 2003). These findings are in line with those showing that minority-group members highly identified with their ingroup were more vulnerable to the effect of perceived discrimination or other social threats (Bagci et al, 2018b; Eccleston & Major, 2006; Major, Quinton, & Schmader, 2003; McCoy & Major, 2003; Noh, Beiser, Kaspar, Hou, & Rummens, 1999; Yoo & Lee, 2008). Social exclusion would thus greatly affect the psychological condition of those immigrants who are mostly connected and in turn identified with other immigrants.…”
Section: Discussionsupporting
confidence: 91%
“…The result that social connections with the native majority protected from the negative psychological consequences of social exclusion is consistent with existing theories regarding the beneficial power of social connections (Baumeister & Leary, 1995), the advantages of the bridging social capital (e.g., Marschall & Stolle, 2004), and the positive outcomes of intergroup social contact (e.g., Bagci & Turnuklu, 2018). Positive social connections with majority groups may promote a sense of belonging, integration, and acceptance in society, thus protecting devalued minorities from the negative consequences of social exclusion (Bagci, Turnuklu, & Bekmezci, 2018a, 2018b; Mendoza-Denton & Page-Gould, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…25,27 Research evidences of different paradigms showed that intergroup contact may positively relieve loneliness, as both longitudinal and horizontal studies have proved the positive effects of intergroup contact on individual problem-solving, cognitive flexibility, creativity, well-being and mental health in multiple groups, including cross-hukou-regional, ethnic, gender and country. 26,[28][29][30][31][32][33][34][35][36] Specifically, an intergenerational technology program brings disparate age groups together to interact in meaningful activities, resulting in effectively reducing loneliness for older adults. 29 Our hypothesis thus is that intergroup contact may alleviate loneliness.…”
Section: Lonelinessmentioning
confidence: 99%
“…Research examining these processes at an intergroup level have mainly investigated cross‐group friendship and demonstrated some positive effects. For example, cross‐group friendships have been found to be associated with improved psychological health and well‐being of adults with physical disabilities (Bagci et al., 2018), protected psychological well‐being of adolescents and children from the negative consequences of perceived ethnic discrimination (Bagci et al., 2014; Benner & Wang, 2017) and negative contact (Paolini et al., 2014), improved college students’ institutional belongingness and satisfaction (Mendoza‐Denton & Page‐Gould, 2008), improved psychological well‐being in both minority and majority students, via self‐disclosure and self‐affirmation (Bagci et al., 2017). There is also some evidence, however, that cross‐group friendship can be negatively associated with health and well‐being.…”
Section: Intimate Contact As a Social Cure Or Social Cursementioning
confidence: 99%